DERIVATIONAL AND INFLECTIONAL MORPHEMES IN ENGLISH AND JAVANESE - Ihsani Diah Anjariah; Anni Holila Pulungan; Rahmad . Husein (LINGUISTIK TERAPAN, 2022)
ABSTRACT This study is about the realization of derivational and inflectional morphemes in English and Javanese. The objectives of this study are to investigate the kinds of derivational and inflectional in English and Javanese short stories, how the English and Javanese words formed by derivational and inflectional, and to explain the realization of derivational and inflectional morphemes in English and Javanese. This study is designed in descriptive-qualitative research. The source of data is English and Javanese short stories namely 1) Oedipus Rex and Sangkuriang, 2) Beauty and the beast and Lutung Kasarung. The data of the study is the words of English and Javanese. The findings of the study showed that the word formation formed by derivational morpheme in English short stories were begun from Oedipus rex consisted of 11 noun formation, 1 verb formation, 2 adjective formation and 8 adverb formation. While, beauty and the beast consisted of 16 noun formation, 2 verb formation, 9 adjective formation, and 14 adverb formation. The total of derivational process in Oedipus Rex and beauty and the beast was 63 words (52%). The word formation formed by derivational morpheme in Javanese short stories were begun from Sangkuriang consisted of 17 noun formation, 16 verb formation, and 1 adverb formation. While, Lutung Kasarung had 3 noun formation, 16 verb formation, 1 adjective formation, and 4 adverb formation. The total of derivational process in sangkuriang and Lutung Kasarung was 58 words (48%). The word formation formed by inflectional morpheme in English short stories were begun from Oedipus Rex had 1 noun formation, 27 verb formation, and 2 adjective formation. While, Beauty and the Beast had 12 noun formation, 36 verb formation, and 14 adjective formation. The total was 92 words (100%). Javanese did not have inflectional process.